IMPLEMENTATION OF THE KAKAWIN RAMAYANA VALUE IN THE NGABEN CEREMONY IN BALI - Ida Ayu Tary Puspa; Ida Bagus Subrahmaniam Saitya (Samā Jiva Jnānam (International Journal of Social Studies), 2025)
Ramayana in the Weda is part of the Weda Smrti, precisely part of Itihasa. The presence of Ramayana as a foundation in carrying out life has been implemented in ceremonies, one of which is the ngaben ceremony. Ramayana for Balinese Hindus is known in the form of kakawin, namely poetry containing wirama with guru and laghu. At the ngaben ceremony in the mabebasan tradition, there will be someone singing the kakawin Ramayana at the funeral home. When bathing the body of a series of ngaben ceremonies, there will be someone singing it in the wirama Wangsastha/Swandewi (Sargah XXIV p.486). The values ​​contained in the Kakawin Ramayana such as the values ​​of dharma, bhakti, moksa should be used as a guide in life in this world. Therefore, in living life, dharma should guide every step, including realizing an attitude of devotion to God and fellow human beings. Thus, the Kakawin Ramayana provides guidance to Hindus in this life.